PENJATUHAN PIDANA DENDA TERHADAP ANAK YANG BERKONFLIK HUKUM DALAM PERKARA TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Putri, Rindu Yusticia Puspaning; Nainggolan, Marsudin; Basuki, Basuki (SINERGI : Jurnal Riset Ilmiah, 2025)
Children have a strategic position in ensuring the survival of a nation, so that legal protection for children is a state obligation as stated in Article 28B paragraph (2) of the 1945 Republic of Indonesia Constitution and the Convention on the Rights of the Child which has been ratified through Presidential Decree Number 36 of 1990. In the context of criminal justice, children involved in narcotics crimes must receive legal treatment in accordance with the principle of the best interests of the child. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System has regulated that for children who are sentenced to imprisonment and fines, the fine must be replaced with job training. However, in practice, there is still a discrepancy between normative provisions (das Sollen) and the reality of law enforcement (das Sein), such as in Decision Number 1/Pid.Sus-Anak/2014/PN.Pli and Decision Number 98/Pid.Sus-Anak/2020/PN.Plg, which imposes a fine on children without applying a substitute punishment in the form of job training as mandated by the SPPA Law. The formulation of the problem raised in this study is how the criminalization system for children in conflict with the law in cases of drug abuse and how to enforce the law against children in conflict with the law in cases of drug abuse. In this study, the author uses the double track system theory and law enforcement theory as analytical tools in this study. The research method used is a normative legal approach. This study uses a statute approach, a case approach, a conceptual approach, and an analytical approach, which in principle are sourced from primary legal materials consisting of laws and judges' decisions, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques.. The results of the study on the punishment of children in several cases of drug abuse have not fully implemented the principle of restorative justice as mandated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA), this shows a disparity in court decisions. In several cases, children who were proven to be abusers were sentenced to prison and large fines, while in other cases children who acted as couriers or intermediaries were not subject to fines. The suggestion in this study is that it is necessary to harmonize and synchronize Law Number 35 of 2009 concerning Narcotics with Law Number 11 of 2012 concerning SPPA as a legal basis so that there is no longer the application of fines that are not in accordance with special provisions in juvenile justice, and in addition, it is necessary to increase the capacity and understanding of law enforcement officers, both investigators, public prosecutors, and judges, regarding the application of the principle of the double track system and restorative justice in handling child cases, especially in cases of drug abuse